Ambientes de aprendizaje lúdicos en el nivel inicial II - Mejía Guanga, Jissela Yajaira (2017)
The purpose of the present investigation was to express the need for the existence of playful learning environments in the initial level, which allowed the development in the auditory, visual, motor, playful, cognitive, social and especially language levels both intellectual and emotional development of children in today's societies, hence the importance of reinforcing these spaces within the classroom, from diverse and complex perspectives that do not reduce their dimensions. The same will be worked on in the playful aspect, pointing out axes to turn to a deeper reflection on the current education. These disciplines are related to didactic purposes that link the current theories, so they are also called educational environments or playful corners. For the preparation of the present document was based on a qualitative methodology because it seeks the solution to a socioeducative problem. The results obtained through the field work applying techniques such as the interview, the survey and the observation that will allow to give a value judgment on the study problem, in this case the use of the learning environments; these data will later enable us to recommend actions to overcome institutional failures; in this way the project will generate a practical pedagogical and curricular contribution that will have a positive impact on the socio-educational scope of the educational community. In conclusion, this study shows how learning environments will serve significantly to students entering this level, it should be emphasized that certain aspects must be improved within the classroom to achieve better teaching, which will be achieved little by little.